2004
DOI: 10.1016/j.otohns.2004.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Laryngeal Nerve Integrity Monitoring During Thyroidectomy: Does it Reduce Risk of Injury?

Abstract: There were no statistically significant differences in RLN paralysis, paresis, or total injury rates between control and NIM groups, even in subsets with advanced T-stage and increased baseline risk. Advanced T-stage is a significant predictor of RLN paresis in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 18 publications
3
67
2
2
Order By: Relevance
“…Several studies show a small reduction in RLNP incidence using IONM, but fail to exhibit statistical significance when compared with direct visualization alone. 6,12,13,17,[49][50][51][52][53][54] The one published randomized control trial comparing IONM versus identification alone in bilateral thyroid surgery concluded that IONM reduced rates of transient but not permanent palsies. 55 The recent meta-analysis by Higgins et al analysed 56 There are some instances where evidence for IONM use is stronger, suggesting that it can aid in the identification of the nerve, correlating with decreased complication rates.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…Several studies show a small reduction in RLNP incidence using IONM, but fail to exhibit statistical significance when compared with direct visualization alone. 6,12,13,17,[49][50][51][52][53][54] The one published randomized control trial comparing IONM versus identification alone in bilateral thyroid surgery concluded that IONM reduced rates of transient but not permanent palsies. 55 The recent meta-analysis by Higgins et al analysed 56 There are some instances where evidence for IONM use is stronger, suggesting that it can aid in the identification of the nerve, correlating with decreased complication rates.…”
Section: The Role Of Ionmmentioning
confidence: 99%
“…When the definitive diagnosis is consistent with malignancy, patients typically undergo a second surgical procedure in the form of a completion thyroidectomy. Furthermore, because 50% to 80% of indeterminate lesions are benign on final pathology, a significant number of patients undergo potentially avoidable surgery with its inherent risks and costs (2,5,6). Although many immunohistochemical and molecular markers have been investigated in recent years in efforts to improve sensitivity and specificity of FNA cytology, none has yet been accepted as integral to the diagnostic armamentarium by clinicians and cytopathologists.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic ventriculocordectomy, or arytenoidectomy are the surgical procedures of choice for such patients. The use of electrophysiological monitoring of RLN during thyroid surgery has been mentioned in the literature in high risk cases to avoid inuring the nerve [1,9] To conclude, bi-lateral vocal cord palsy is a rare but possible complication in the course of recurrent thyroid surgery, total thyroidectomy, or thyroid carcinoma. Knowledge about the risk factors contributing to this complication, might increase awareness for such an event, thus allowing early intervention to avert adverse or fatal outcomes.…”
Section: Redo Surgery and Ligature Of The Inferior Thyroid Artery [10mentioning
confidence: 99%
“…Better preoperative preparation and proper surgical techniques of thyroidectomy have minimized complications to less than 2-3%. Bilateral recurrent nerve palsy is the rarest of all complications, with a reported incidence varying between 0.4% to 14 %, but can be potentially fatal if missed [1,2].We report a case in which the patient experienced life threatening stridor and severe dyspnoea requiring re-intubation few minutes after extubation.Keywords: Vocal cord palsy, total thyroidectomy, airway obstruction. …”
mentioning
confidence: 92%
See 1 more Smart Citation